Faktor-faktor yang Mempengaruhi Tax Avoidance pada Perusahaan Properti dan Real Estate di Bursa Efek Indonesia Periode 2019 – 2022 - Bonita, Brigitta Valencia; Suhartono, Sugi (Global Research on Economy, Business, Communication, and Information, 2024)
Taxes for companies are a burden that can reduce company profits, while taxes for the state are revenues that will be used to finance state spending. This difference in interests causes managers to avoid taxes. The aim of this research is to determine the effect of profitability, capital intensity, inventory intensity, leverage, and company size on tax avoidance in property and real estate sector companies listed on the Indonesia Stock Exchange in the 2019 - 2022 period. There are 11 property and real estate companies who meet the criteria for taking samples for testing. This research uses SPSS 26 to carry out data analysis such as descriptive statistical analysis, pooling test, classical assumption test, multiple liner regression test, and hypothesis testing. The conclusion in this research is that profitability, capital intensity and inventory intensity have no effect on tax avoidance, leverage and company size have an effect on tax avoidance.